Leitura de imagens na sala de aula: relações entre saberes, práticas de professores de arte e grupos de estudos - Sousa, Marcia Maria de (2006)
The image in the contemporaneous is a vehicle of communication and expression that permits a multiplicity of relations between subjects, collaborating in many ways for the construction of knowledge about reality and about ourselves. The importance of this image is the beginning of this work that has as objective to analyze the relation between the Art teachers education and the comprehension that this teacher has of conceptual and methodological aspects relative to the reading of guiding images of the knowledge and practical production that characterizes his work in the classroom. We situate the focus of our investigation in the classroom practices of a visual/plastic art teacher who works in the municipal teaching net of Uberlândia and also participates of two local Art professors study groups: one in the Municipal Center of Educational Study and Project Julieta Diniz (CEMEPE) which is connected to the Municipal Secretary of Education and the other, the Art Teaching Research Nucleus (NUEPA) that is linked to the Plastic Arts Department of the Federal University of Uberlândia (UFU). In this work, the qualitative approach presents itself as a research methodology that permits a dialogue between the actions realized in the study groups and the teacher acting concerned to the image reading practices. In this way, we search to know and analyze, under the teacher s point of view, the role of the study groups in two different ways: in the deepen of the methodological and theoretical issues related to the plastic/visual art teaching and the professionals awareness of that teaching area to elucidate the necessity of promoting significant images readings in the interaction with his students.